Association between pyrethroid insecticide exposure and pulmonary function among school-aged children - Lihua QIAN; Yi HU; Peipei HU; Guodong DING (环境与职业医学)
BackgroundPrior epidemiological studies suggest that exposure to pyrethroid insecticides may adversely affect children’s respiratory health. However, only limited studies are currently available on this topic in China. ObjectiveTo explore the association between exposure to pyrethroid insecticides and pulmonary function in children in Shanghai. MethodsFrom August 2019 to January 2020, a cross-sectional study was conducted, recruiting 163 healthy school-aged children (aged 5–12 years) from Shanghai Children’s Hospital, Shanghai Jiao Tong University School of Medicine. Basic information, including age, height, weight, and family income, was collected. Urine samples from the children were collected and were analyzed for the levels of three pyrethroid insecticide metabolites: 3-phenoxybenzoic acid (3-PBA), cis-3-(2,2-dichlorovinyl)-2,2-dimethylcyclopropane carboxylic acid (CDCCA), and trans-3-(2,2-dichlorovinyl)-2,2-dimethylcyclopropane carboxylic acid (TDCCA). Gas chromatography-tandem mass spectrometry (GC-MS/MS) was used for the analysis. Spirometry was used to assess pulmonary function and recorded following parameters: peak expiratory flow (PEF), forced expiratory flow between the 25th and 75th percentiles of forced vital capacity (FEF25-75), forced expiratory volume in one second (FEV1), forced vital capacity (FVC), and FEV1/FVC. Multiple linear regression and restricted cubic spline models were used to evaluate the associations between urinary pyrethroid insecticide metabolite levels and pulmonary function parameters. ResultsThe study included 163 school-aged children, with an average age of (7.04 ± 2.08) years and an average body mass index (BMI) of (16.04 ± 2.72) kg·m−2; 75 (46.01%) of the participants were boys. The detection rates of 3-PBA, TDCCA, and CDCCA in urine were 85.28%, 17.79%, and 4.91%, respectively. The median creatinine-adjusted 3-PBA concentration was 0.150 μg·g−1. After adjusting for confounders such as height, BMI, sex, age, delivery mode, annual family income, and maternal education level, the multiple linear regression model showed that urinary 3-PBA levels were negatively associated with both FVC [β=−0.030, 95% confidence interval (CI): −0.058, −0.003; P=0.031] and FEV1 (β=−0.032, 95%CI: −0.064, 0.000; P=0.04998). The final restricted cubic spline model showed a nonlinear association between urinary 3-PBA levels and FVC, FEV1, PEF, and FEF25-75（P for nonlinear < 0.05；P for overall < 0.05）. ConclusionThe level of pyrethroid insecticide exposure in school-aged children in Shanghai is relatively high. The urinary 3-PBA concentration is negatively associated with pulmonary function, indicating potential adverse effects of pyrethroid insecticide exposure on respiratory health of school-aged children.